Prophylactic Activity of Orally Administered FliD-Reactive Monoclonal SIgA Against Campylobacter Infection - Perruzza, Lisa; Jaconi, Stefano; Lombardo, Gloria; Pinna, Debora; Strati, Francesco; Morone, Diego; Seehusen, Frauke; Hu, Yue; Bajoria, Sakshi; Xiong, Jian; Kumru, Ozan Selahattin; Joshi, Sangeeta Bagai; et al. (Frontiers in Immunology, 2020)
Campylobacter infection is one of the most common cause of bacterial gastroenteritis world-wide and a major global health threat due to the rapid development of antibiotic resistance. Currently, there are no vaccines approved to prevent campylobacteriosis and rehydration is the main form of therapy. Secretory IgA (SIgA) is the main antibody class found in mucous secretions, including human milk, and serves as the first line of defence for the gastrointestinal epithelium against enteric pathogens. In this study, we describe the prophylactic activity of orally delivered recombinant SIgA generated from two human monoclonal antibodies (CAA1 and CCG4) isolated for their reactivity against the flagellar-capping protein FliD, which is essential for bacteria motility and highly conserved across Campylobacter species associated with severe enteritis. In an immunocompetent weaned mouse model, a single oral administration of FliD-reactive SIgA CAA1 or CCG4 at 2 hours before infection significantly enhances Campylobacter clearance at early stages post-infection, reducing the levels of inflammation markers associated with epithelial damage and polymorphonuclear (PMN) cells infiltration in the caecum lamina propria. Our data indicate that the prophylactic activity of CAA1 and CCG4 is not only dependent on the specificity to FliD, but also on the use of the SIgA format, as the IgG versions of the same antibodies did not confer a comparable protective effect. Our work emphasizes the potential of FliD as a target for the development of vaccines and supports the concept that orally administered FliD-reactive SIgA can be developed to prevent or mitigate the severity of Campylobacter infections as well as the development of post-infection syndromes.